Amaranth in Mexico: old productive strategies and new consumers - Sánchez, Kim (2018)
Based on the results of a case study in the town of Huazulco, Morelos (Central Mexico), on artisan workshops and small business that are dedicated to produce traditional amaranth sweets, we reflect on the current development of this agro-food chain. Amaranth is an ancestral product that contains a high nutritional value, which in pre-Hispanic times had a high consumption and ritual value, but after the conquest it was limited and keep for centuries a reduced presence. However, in the last decades the area planted with amaranth in the country quadrupled and increased its national and exportation demands. This apogee is related to changes in food patterns and the segmentation of the global agro-food market. The potential impact and benefit of the boom in amaranth production and demand differentiation for peasants, local rooting agro industries and rural communities such as Huazulco in Mexico is discussed.